Most common ergonomic injuries among healthcare workers - Alharbi, Shada M.; Alghanem, Abdullah K.; Alessa, Hanan A.; Aldoobi, Raghad S.; Busayli, Fatimah A.; Alharbi, Karam S.; Alzahrani, Abdulrahman S.; Kashkari, Khalid A.; Huraib, Mohammad M.; Harbi, Shatha S. A.; Higazy, Yousra E. (International Journal Of Community Medicine And Public Health, 2021)
In the different healthcare settings, evidence shows that healthcare workers can be exposed to various work-related hazards, which might be ergonomics, biological, psychological, and physical hazards. Work-related musculoskeletal disorders are frequently reported among the different healthcare workers, and estimates indicate that surgeons are the most commonly affected. Disorders and injuries related to the backbone, shoulders, wrist, and knees are mainly reported by healthcare workers as relevant ergonomic hazards. In the present literature review, we have discussed the commonest ergonomics that have been reported in the literature among healthcare workers. Musculoskeletal disorders as back, knee, and wrist pain are the most frequently reported among the different settings. We have also assessed the different reasons that might attribute to the development of such events, and increased workload and working hours, in addition to the harmful postures are the main reasons that have been reported in the literature. Each clinical and surgical setting might be associated with significant risk factors over others, and therefore, specific interventions should be applied within these settings to enhance satisfaction among healthcare workers. Healthcare authorities are mainly responsible to achieve this. However, further epidemiological investigations are still needed to adequately plan the righteous interventional programs.